(untitled) (Emancipação, 2020)
This study analyzes the representation of Teko Porã in the poetry of Brígido Bogado from the perspective of ecocritical studies. Such representation indicates the indigenous cosmovision based on the ancestral language and knowledge that are presented underlying the work of the author and exposes the criticism of the depredation of nature carried forward by the society of capital and the alienation of human relations that have been imposed since the colonization of the area, bodies and minds in America, as pointed out by Aníbal Quijano (2000). The article by Meliá (2015) “El buen vivir se aprende” addresses the complexity of this term, the teko porã, in Guarani’s culture. It is further observed in these works the possibility to rethink ecocritical studies from a Latin American perspective, according to Flores (2017), which reveals other ways of knowing and another relationship between humans and nature that dispenses the means of dominance established by Western hegemonic groups to the present day.